Instability simulation of the submerged anti-dip slope based on the CFD-DEM coupling method - Xie, Liangfu; Zhu, Qingyang; Ge, Ying; Qin, Yongjun (Frontiers in Earth Science, 2023)
More and more underwater-related geotechnical problems have arisen, but there is little research about the instability process of submerged anti-dip slopes. This paper builds the CFD-DEM coupling method based on the CFD solver OpenFOAM and the DEM solver PFC. The Ergun Test is selected as the benchmark test to verify the accuracy of the coupling method, and the pressure drop predicted from the coupling method agrees well with the analytic solution. Then we build a numerical submerged anti-dip slope model and a special effort is made to study its instability characteristic. The flow of water will weaken the slope stability, and the birth of cracks will be accelerated. The drag force will restrain the toppling deformation, resulting in a deeper fracture surface. Then we changed the joint thickness and joint angle to study its effect on the slope stability. The collapse load increases with the joint thickness and the form of toppling deformation changes from flexural failure to block failure. The collapse load increase with the joint dip decreasing, and the position of the damaged area becomes higher, the angle between the bottom fracture surface and the vertical line to joints get smaller with the joint dip decreasing.